FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA PEMANEN PADA PT. CERENTI SUBUR KABUPATEN KUANTAN SINGINGI - Rizki Dwi Purwati; Nariman Hadi; Mashadi Mashadi (Fakultas Pertanian, Universitas Riau, 2019)
The purpose of this study was to determine how the economic productivity of labor and technical productivity of oil palm harvester at PT Cerenti Subur and to determine how much influence social and economic factors of age, number of dependents, work experience, ethnicity, education level, and incentive / premium on labor productivity of oil palm harvester at PT. Cerenti Subur at Kuantan Singingi District. The analytical method used is the method of Mathematical and multiple linear regression analysis. Results obtained showed that the economic productivity of labor in the oil palm harvest of PT. Cerenti has an average of IDR 146 133 per day and average technical productivity is of 2,474 Kg per day. The relationship between labor productivity of harvester in PT. Cerenti has a significant effect on labor productivity with a significant F test of 0.000 and has R square value of 0.919 which means that relationship between productivity factor of age, number of dependents, work experience, ethnicity, level of education and incentives is 91.9% while the rest 8.1% of labor productivity of oil palm harvester at PT Cerenti were influenced by other factors which were not included in the models studied.